Persistence of The Tarekat Naqsabandiyah in Local Politics of Indonesia Post New Order - Tito Handoko; Abdul Munir Mulkan; Mega Hidayati; Muhammad Azhar (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
In the Indonesian context, tarekat is seen as a social movement with a broad impact. Its existence and activity need to be paid attention to by the State, society, and other political infrastructure. Many experts have carried out the discourse on tarekat with various points of view. This study focuses on the socio-political sphere of tarekat and its movements in local Indonesian politics after the Soeharto Era using a qualitative approach with interpretive data analysis involving the informants who understand the tarekat activity in Rokan Hulu in depth. The emergence of spiritual organs with various ideological variants, visions, and missions indicates the strengthening of civil supremacy in Indonesia. As part of a religious civil society organization, the Naqsyabandiyah order can grow and exert a strong influence on the dynamics of Indonesian local democracy, especially in Rokan Hulu - Riau. The existence of this movement strengthens Bruinessen's argument about the tarekat as a "storehouse of sounds," whose symbolization of motion is described by the gesture and commands of the teacher. After the New Order, there was a shift in the political orientation of this group; the nature of taqlid to master teachers was only for religious matters, while on political issues, there was a shift in direction that was more directed at the individual interests of the congregation. Even so, the Naqsyabandiyah Rokan Hulu tarekat could still maintain its existence and political power.